2019
DOI: 10.1080/15592294.2019.1695340
|View full text |Cite
|
Sign up to set email alerts
|

Race-specific alterations in DNA methylation among middle-aged African Americans and Whites with metabolic syndrome

Abstract: Metabolic syndrome (MetS) is a cluster of cardiometabolic risk factors for all-cause mortality, cardiovascular disease, and cancer. Identifying epigenetic alterations associated with MetS in African Americans (AAs) and Whites may provide insight into genes that influence its differential health outcomes. We examined DNA methylation (DNAm) and performed an epigenome-wide association study (EWAS) of MetS among AAs and Whites with and without MetS. We assessed age, race and poverty status associated DNAm among AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 72 publications
0
39
0
Order By: Relevance
“…Our EWAS revealed 161 replicated associations between 16 CpG sites in eleven loci and 57 unique metabolic measures. All of the eleven epigenetic loci have been previously found to be associated with metabolic traits and processes, primarily based on clinical and biochemical measurements of composite blood lipids [ 14 20 , 22 25 , 29 , 37 , 38 , 42 , 43 ]. Here, we uncover novel findings with regard to specific features of lipoprotein subclasses such as the lipid compositions and concentrations of each type of lipid in lipoproteins, giving deeper insights into the underlying biology of previous associations.…”
Section: Discussionmentioning
confidence: 99%
“…Our EWAS revealed 161 replicated associations between 16 CpG sites in eleven loci and 57 unique metabolic measures. All of the eleven epigenetic loci have been previously found to be associated with metabolic traits and processes, primarily based on clinical and biochemical measurements of composite blood lipids [ 14 20 , 22 25 , 29 , 37 , 38 , 42 , 43 ]. Here, we uncover novel findings with regard to specific features of lipoprotein subclasses such as the lipid compositions and concentrations of each type of lipid in lipoproteins, giving deeper insights into the underlying biology of previous associations.…”
Section: Discussionmentioning
confidence: 99%
“…The association between aberrant DNA methylation and disease state has been studied across various disorders, including CVDs, autoimmune disorders and various cancers [ 22 , 23 ]. In recent years, epigenome-wide association studies (EWASs) have identified global and locus-specific epigenetic changes potentially involved in the pathophysiological mechanisms responsible for the development of MetS ( Table 1 ) [ 24 , 25 ]. For example, an EWAS study performed in individuals with MetS demonstrated decreased methylation of CPT1A, a gene with a key role in regulating mitochondrial fatty acid oxidation (FAO), to be correlated with the increased metabolic risk and overall MetS phenotype [ 25 ].…”
Section: The Classical Epigenetic Mechanisms In Metsmentioning
confidence: 99%
“…In recent years, epigenome-wide association studies (EWASs) have identified global and locus-specific epigenetic changes potentially involved in the pathophysiological mechanisms responsible for the development of MetS ( Table 1 ) [ 24 , 25 ]. For example, an EWAS study performed in individuals with MetS demonstrated decreased methylation of CPT1A, a gene with a key role in regulating mitochondrial fatty acid oxidation (FAO), to be correlated with the increased metabolic risk and overall MetS phenotype [ 25 ]. In a recent EWAS study in African American adults, MetS was consistently associated with increased methylation in the ABCG1, a gene that encodes a protein in the ATP-binding cassette transporter family and is involved in intra- and extra-cellular signalling and lipid transport [ 24 , 26 ].…”
Section: The Classical Epigenetic Mechanisms In Metsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetics and environmental exposures both influence phenotype, partly through epigenetic modifications. Genetic architecture affects DNAm in terms of the availability of cytosine-phosphate-guanine (CpG) sites, the efficacy of methylation-related enzyme expression [8,11], how DNAm responds to exposure [12] and inherent NCD risk [2]. Environmental exposures can be either external (behavioral or lifestyle-related factors such as diet, exercise and air purity) or internal (metabolic and biochemical factors such as inflammation and adiposity).…”
Section: Contextualizing Methylationmentioning
confidence: 99%